Cercospora Leaf Spot of Rose - Jozer Mangandi; Natalia A. Peres (EDIS)
PP267, a 4-page illustrated fact sheet by Jozer Mangandi and Natalia A. Peres, describes this little-investigated disease that is one of the primary foliar diseases of roses in Florida — causal agent and geographic distribution, symptoms and control. Published by the UF Department of Plant Pathology, May 2009.